The Three-Dimensional Signal Collection Field for Fiber Photometry in Brain Tissue - Pisanello, Marco; Pisano, Filippo; Hyun, Minsuk; Maglie, Emanuela; Balena, Antonio; De Vittorio, Massimo; Sabatini, Bernardo L.; Pisanello, Ferruccio (Frontiers in Neuroscience, 2019)
Fiber photometry is used to monitor signals from fluorescent indicators in genetically-defined neural populations in behaving animals. Recently, fiber photometry has rapidly expanded and it now provides researchers with increasingly powerful means to record neural dynamics and neuromodulatory action. However, it is not clear how to select the optimal fiber optic given the constraints and goals of a particu-lar experiment. Here, using combined confocal/2-photon microscope, we quantitatively characterize the fluorescence collection properties of various optical fibers in brain tissue. We show that the fiber size plays a major role in defining the volume of the optically sampled brain region, whereas numerical aper-ture impacts the total amount of collected signal and, marginally, the shape and size of the collection volume. We show that approximately 80% of the effective signal arises from a 105-106 µm3 volume ex-tending ~200 µm from the fiber facet for 200 µm core optical fibers. Together with analytical and ray tracing collection maps, our results reveal the light collection properties of different optical fibers in brain tissue, allowing for an accurate selection of the fibers for photometry and helping for a more pre-cise interpretation of measurements in terms of sampled volume.